Which drug for the adult epileptic patient: phenytoin or valproate?. Issue 6471 (16th March 1985) - Turnbull, D M; Howel, D; Rawlins, M D; Chadwick, D W
Abstract : A series of 140 previously untreated patients with tonic-clonic or partial seizures were randomised to receive either phenytoin or sodium valproate. There was no difference between the treatment groups in pretreatment variables that might influence outcome. Sodium valproate and phenytoin in the treatment of tonic-clonic or partial seizures showed no difference in efficacy as regards time to two year remission or time to first seizure. When the possible prognostic factors were studied, including history and results of clinical examination and investigations before treatment; the only factor which influenced the proportion of patients achieving two year remission was type of seizure. Patients with a clinical history of partial seizures did significantly less well than those with a history of tonic-clonic seizures only. This study showed no major difference in efficacy between sodium valproate and phenytoin in adults with recent onset of epilepsy, irrespective of the type of seizures that the patient suffered.